DLD - Lecture5 (Completed)
DLD - Lecture5 (Completed)
DLD - Lecture5 (Completed)
ECE2002
Reference Books:
1. Mandal ”Digital Electronics Principles & Application, McGraw Hill
Edu,2013.
2. Comer “Digital Logic & State Machine Design, Oxford, 2012.
3. William Keitz, Digital Electronics-A Practical Approach with
VHDL,Pearson,2013
Unit:1
Digital Logic
Design
Fundamentals
The operator precedence for evaluating Boolean expressions is (1) parentheses, (2) NOT, (3) AND,
(4) OR
Literals, Variables and Terms
F2= X’Y’Z + X’YZ + XY’
Variables = (X, Y, Z)
Literals = (X’, Y’, Z, X’, Y, Z, X, Y’)
Terms =(2 NOT term, 3 AND term and 1 OR term)
Minimization
Minimization means reducing the number of literals. We can minimize the expression
with the help of postulates and theorems.
(A+B+C+D+……..F)’ = A’B’C’D’…….F’
(ABCD..F)’ = A’+ B’+ C’+ D’ + ……. + F’
Examples
Find the complement of the functions F1= X’YZ’ + X’Y’Z and F2= X(Y’Z’ +YZ) by applying
DeMorgan’s theorem:
Exp. You have given the following expression and asked to represent it in sum of
minterms form
F = (A’+B)(A+B’) ------ POS Form
= A’.A+A’.B’+AB+B.B’ -------(Multiply the product)
= A’B’+AB --------(A.A’=0,B.B’=0) (SOP Form)
To convert SOP to POS, we use distributive law
Three binary variable minterms and
maxterms
Example
Express the Boolean function F= A+ B’C as a sum of minterms.
Sol: The function has three variables, A,B and C. The first term A is missing two
variables; therefore,
A= A(B+B’) = AB + AB’
The function is still missing C variable so,
AB(C+C’)+ AB’(C+C’) = ABC + ABC’ + AB’C + AB’C’
The second term B’C is missing A variable; hence,
B’C = B’C(A+A’) = AB’C + A’B’C
Combining all, F = ABC + ABC’ + AB’C + AB’C’ + A’B’C
= A’B’C + AB’C’ + AB’C + ABC’ + ABC
= m1 + m4 + m5 + m6 + m7 F(A,B,C) = (SOP)
Example
Express the Boolean function F= XY + X’Z as a product of maxterms.
Sol: F = (A+B)(A+B’)(A’+B)(A’+B’)
= (A + B.B’)(A’ + B.B’)
= (A + 0)(A’ +0)
= A.A’
=0
Example
P6) Simplify F = A(B+C’((AB)’ (AC’)’))
Sol: F = A + B[AC+(B+C’)D]
= A + B(AC+BD+C’D)
= A + BAC + BBD + BC’D
= A(1+BC) + BD(1+C’)
= A.1 + BD.1
= A + BD